Impact of neurotransmitters, emotional intelligence and personality on investor's behavior and investment decisions - Mumtaz Ahmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Mainstream of the investors and investment advisory consultants suggest and focus on standard finance models and do not take into account the behavioral and neurological dimensions of finance as neurotransmitters, emotional intelligence and personality of investors. These aspects of individual investors can cause of several mistakes while investing in stock market. The primary data of 455 investors from Pakistan Stock Exchanges is used for analysis. The data analysis performed with the help of Hierarchical Latent Variable Models in PLS-SEM by using the reflective-formative type constructs as guided by Becker et al., (2012). The empirical evidence of the study reveals that personality dimensions especially openness and consciousness as well as emotional intelligence dimensions especially self emotions apraisal and regulation of emotions have significant relations with the behavioral features of investor especially investment horizon, personalization of loss and control level. Similarly, neurotransmitter's dimensions dopamine and epinephrine have significant relation with investment decisions of indiviual investors. In view of this, emotional intelligence, neurotransmitters and personality collectively have 13.2% impact on ivestor behavior and these dimensions collectively have 4.1% impact on investment decisions of individual investor. The study opens new horizon by providing supplemented inner view of investor's behavior and their decision's in the stock market of Pakistan and demands more effort to determine universal latent constructs for combine model of neurofinance and behavioral finance. However, limitation of study is that it does not analyze the current model beyond the current sample size for stock market of other regions of the world.
Keywords: 330; neuro-finance; behavioral finance; neurotransmitters; emotional intelligence and personality